Momento para escuchar = Listening time - Verdick, Elizabeth; Heinlen, Marieka; Rojas, Edgar; Verdick, Elizabeth; Verdick, Elizabeth (Golden Valley, MN : Free Spirit Publishing, 2016)
"Learning valuable social skills like listening can happen even at an early age. "Put away the wiggles. Put away the giggles. Listening works better when your body's calm and still." When it's time for young children to listen closely, this bilingual board book sets the tone. They discover that it's important to open their eyes and ears but to close their mouths ("zip it, lock it, put it in your pocket") so good listening can begin"--
"Bilingual (English/Spanish) board book helps teach listening skills to toddlers. Includes tips for parents and caregivers"--
Cover title.
On board pages.
"Translation by Edgar Rojas."
Age 0-4.
In English and Spanish.
Keywords: Listening -- Juvenile literature; Escuchar -- Literatura juvenil